The effects of engineering design processes on spatial abilities of middle school students - ÖZDEMİR, AHMET ŞÜKRÜ (SPRINGER, 2020)
The spatial ability is defined as the combination of some abilities such as imagining the movements of objects, mental rotation, and spatial transformations. Students' spatial abilities can be enhanced through specific education programs. This study investigated the effects of engineering design-based instruction on spatial abilities of 8th grade students. The study was conducted with a total of 75 students: two experimental groups (n = 35) and two control groups (n = 40). Three different engineering design modules were developed. Using a mixed method approach, qualitative data were analysed to identify students' engineering design processes. In the quantitative part of the study, a quasi-experiment was used to examine the effects of engineering design-based mathematical activities on spatial abilities of students. Results revealed that engineering design-based activities positively affect the development of students' spatial abilities. In addition, findings related to the qualitative data on students' design processes were presented; and suggestions for further research were introduced.
Keywords: Design processes; Engineering design-based instruction; Middle school students; Spatial ability; SCIENCE; STEM; THINKING; OBJECTS; IMPACT